2010
DOI: 10.1002/bdra.20700
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variants in COL2A1, COL11A2, and IRF6 contribute risk to nonsyndromic cleft palate

Abstract: This study provides for the first time evidence of the implication of IRF6, COL2A1, and WNT3 in the occurrence of NSCP. It is likely that variation in cartilage collagen II and XI genes, IRF6, and the Wnt and FGF signaling pathway genes contributes susceptibility to nonsyndromic cleft palate in Northeastern European populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
43
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 43 publications
0
43
0
Order By: Relevance
“…COL11A2 is one of three distinct genes that encode collagen XI, which is expressed in the developing jaw in rats [43]. Genetic variants in COL11A2 can cause syndromic and non-syndromic palatal defects [44, 45]. …”
Section: Discussionmentioning
confidence: 99%
“…COL11A2 is one of three distinct genes that encode collagen XI, which is expressed in the developing jaw in rats [43]. Genetic variants in COL11A2 can cause syndromic and non-syndromic palatal defects [44, 45]. …”
Section: Discussionmentioning
confidence: 99%
“…Alternations in the synthesis and accumulation of extracellular matrix proteins, including type II, IX, XI collagens, and proteoglycan 10-12 impair palatogenesis, all of that are regulated by Sox9 1,7-9 . Indeed, mutations in or around SOX9 gene result in palatal malformations in human and a mouse model.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have showed that Sox9 induces L-Sox5 and Sox6 transcription, and these Sox proteins coordinately regulate the expression of cartilage-specific extracellular matrix genes, including Col2a1, Col11a2 and Aggrecan 1,7-9 . Genetic variants in these genes also cause palatal malformation 10-12 . These findings indicate that Sox9 transcriptional activity has a regulatory role in palatogenesis.…”
mentioning
confidence: 99%
“…Summing up all of the Zfps in the candidate region, their human homologs are located on 7q11, 11p15, 19p12-13, and 19q13. Among these regions, 19p12-13 has been associated with CLP in a genome-wide linkage study (Vieira et al, 2008) and 19q13 in other studies (Warrington et al, 2006;Nikopensius et al, 2010). The Nlrp genes are also a large family, and the closest human homolog to Nlrp4f appears to be NLRP4, also located on 19q13 (Hamatani et al, 2004).…”
Section: Discussionmentioning
confidence: 93%